Influence of andrographolide on the pharmacokinetics of warfarin in rats - Xiaoli Zhang; Xiaosu Zhang; Xiaocui Wang; Meijun Zhao (Taylor & Francis Group, 2018)
Context: Andrographolide and warfarin are often used together in clinics in China. However, the herb-drug interaction between andrographolide and warfarin is still unknown. Objective: This study investigates the herb-drug interaction between andrographolide and warfarin in vivo and in vitro. Materials and methods: A sensitive and reliable LC-MS/MS method was developed for the determination of warfarin in male Sprague-Dawley rats plasma, and then the pharmacokinetics of orally administered warfarin (0.5 mg/kg) with or without andrographolide (30 mg/kg/day for 7 days) pretreatment was investigated. In addition, Sprague-Dawley rat liver microsomes incubation systems were used to support the in vivo pharmacokinetic data and investigate its potential mechanism. Results: The method validation results showed that a sensitive and reliable LC-MS/MS method was developed for the determination of warfarin in rat plasma samples. The pharmacokinetic results indicated that co-administration of andrographolide could increase the systemic exposure of warfarin significantly, including area under the curve (118.92 ± 18.08 vs. 60.58 ± 9.46 μg × h/mL), maximum plasma concentration (3.32 ± 0.41 vs. 2.35 ± 0.25 μg/mL) and t1/2 (22.73 ± 3.28 vs. 14.27 ± 2.67 h). Additionally, the metabolic stability of warfarin increased from 23.5 ± 4.7 to 38.7 ± 6.1 min with the pretreatment of andrographolide, and the difference was significant (p < 0.05). Discussion and conclusion: In conclusion, andrographolide could increase the systemic exposure of warfarin in rats when andrographolide and warfarin were co-administered, and possibly by slowing down the metabolism of warfarin in rat liver by inhibiting the activity of CYP3A4 or CYP2C9.